Ethnicity and the American short story - Brown, Julie, 1961- (New York : Garland Pub., 1997)
How do different ethnic groups approach the short story form? Do different groups develop culture-related themes? Do oral traditions within a particular culture shape the way in which written stories are told? Why does ""the community"" loom so large in ethnic stories? How do such traditional forms as African American slave narratives or the Chinese talk-story shape the modern short story? Which writers of color should be added to the canon? Why have some minority writers been ignored for such a long time? How does a person of color write for white publishers, editors, and readers?Each
Identity in community in ethnic short story cycles : Amy Tan's The joy luck club, Louise Erdrich's Love medicine, Gloria Naylor's The women of Brewster Place / Rocío G. Davis -- Marking race, marketing race : African American short fiction and the politics of genre, 1933-1946 / Bill Mullen -- Womanist storytelling : the voice of the vernacular / Madelyn Jablon -- Minor revolution : Chicano/a composite novels and the limits of genre / Margot Kelley -- Resistance and reinvention in Sandra Cisneros' Woman hollering creek / Susan E. Griffin -- Healing ceremonies : Native American stories of cultural survival / Linda Palmer -- Asian American short stories : dialogizing the Asian American experience / Qun Wang -- Invention of normality in Japanese American internment narratives / John Streamas -- No types of ambiguity : teaching Chinese American texts in Hong Kong / Hardy C. Wilcoxon -- "Wavering" images : mixed-race identity in the stories of Edith Eaton, Sui Sin Far / Carol Roh-Spaulding -- Resistance and reclamation : Hawaii "pidgin English" and autoethnography in the short stories of Darrell H.Y. Lum / Gail Y. Okawa -- Conflict over privacy in Indo-American short fiction / Laurie Leach -- Re-orienting the subject : Arab American ethnicity in Ramzi M. Salti's The native informant : six tales of defiance from the Arab world / Chris Wise -- Naming of Katz : who am I? who am I supposed to be? who can I be? passing, assimilation, and embodiment in short fiction by Fannie Hurst and Thyra Samter Winslow with a few jokes thrown in and various references to other others / Susan Koppelman.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American fiction -- Minority authors -- History and criticism; Minorities -- United States -- Intellectual life; Short stories, American -- History and criticism; Ethnic groups in literature; Minorities in literature; Ethnicity in literature; Roman américain -- Auteurs issus des minorités -- Histoire et critique; Nouvelles américaines -- Histoire et critique; Groupes ethniques dans la littérature.; Ethnicité dans la littérature.; LITERARY CRITICISM -- American -- General; American fiction -- Minority authors; Ethnic groups in literature; Ethnicity in literature; Minorities in literature; Minorities -- Intellectual life; Short stories, American; United States; Kurzgeschichte; Ethnische Gruppe; USA; Criticism, interpretation, etc